Knockdown Resistance Mutations in Aedes aegypti (Diptera: Culicidae) From Puerto Rico. Issue 6 (4th August 2016) - Ponce-García, Gustavo; Del Río-Galvan, Samantha; Barrera, Roberto; Saavedra-Rodriguez, Karla; Villanueva-Segura, Karina; Felix, Gilberto; Amador, Manuel; Flores, Adriana E.
Abstract: Permethrin resistance is widespread in Aedes aegypti (L.), the main dengue, zika, and chikungunya virus vector in Latin America and the Caribbean. A common mechanism of resistance to pyrethroids—knockdown resistance ( kdr )—is conferred through mutations in the insect's voltage-dependent sodium channel. In this mosquito, around 10 replacement substitutions in the voltage-gated sodium channel gene ( vgsc ) have been reported in pyrethroid-resistant strains. Two of these mutations, named Ile1, 016 and Cys1, 534, are widespread in mosquito populations from Latin America and the Caribbean. This study assessed the levels of permethrin resistance and the frequency of two kdr mutations in eight Ae. aegypti populations collected in Puerto Rico in 2013. Permethrin resistance factors ranged from 33–214-fold relative to the New Orleans reference strain. The frequency of kdr mutation Ile1, 016 ranged from 0.65 to fixation (1.0), and for Cys1, 534 frequencies varied from 0.8 to fixation. Alarmingly, two populations—Carolina and Caguas—reached fixation at both loci. Our results suggest that permethrin effectiveness for Ae. aegypti control is compromised in these collections from Puerto Rico.